Belief about Medications among Sample of Iraqi Patients with Inflammatory Bowel Disease - Nisreen J. Jebur; Dheyaa J. Kadhim; Nawal. M. Firhan (College of Pharmacy University of Baghdad, 2018)
Inflammatory bowel disease includes both Crohn's disease and ulcerative colitis, is a chronic, progressive relapsing disease of gastrointestinal tract that require long-term treatment or maintenance therapy. Taking patient's beliefs about the prescribed medication in consideration had been shown to be an important factor that affects compliance of the patient in whom having positive beliefs is a prerequisite for better compliance. The aim of the current study was to investigate and assess beliefs about medicines among a sample of Iraqi patients with inflammatory bowel disease and to determine possible association between these beliefs and some patient-specific factors. This study is a cross-sectional study carried out on 150 already diagnosed inflammatory bowel disease patients who attended the Gastroenterology and Hepatology Teaching Hospital/Medical City/Baghdad. The mean age of the patients was (31.7 ± 11.4 years).The number of ulcerative colitis patients was 74, while the number of Crohn's disease patients was 76. Belief about medicines was measured using the Arabic version of the beliefs about medicines questionnaire. The majority of the patients (58%) had strong beliefs in the necessity of treatment (specific-necessity score greater than specific-concern). For all patients (ulcerative colitis and Crohn's disease together), there was a significant inverse correlation between male gender and specific concern score. Number of infliximab doses directly correlated with specific necessity score and inversely correlated with specific concern score. Future studies should investigate how interventional approaches addressing these predictors may lead to improve beliefs about medicines among inflammatory bowel disease patients and their impact on disease control.